PENYULUHAN BELA NEGARA BAGI SISWA-SISWI SMPN 11 dan 13 MAGELANG GUNA MENINGKATKAN RASA NASIONALISME - Siswanto, Dwi Joko; Aries Basuki (JURNAL NAGARA BHAKTI, 2023)
The purpose of this community service is to provide state defense counseling to SMPN 11 and 13 Magelang students, with the hope of increasing a sense of nationalism among students. Counseling is carried out using lecture, discussion, and simulation methods. The results of this activity show that students gain a better understanding of the importance of defending the country and a sense of nationalism, and are also able to apply these values in everyday life.